Small-Fiber Polyneuropathy Is Prevalent in Patients With Interstitial Cystitis/Bladder Pain Syndrome. Issue 11 (24th November 2022) - Wolff, Dylan T.; Xu, Raymond; Overholt, Tyler; Bassett, E. Hadley; Ahn, Christine; Simon, Trang; Lee, Peyton; Badlani, Gopal; Matthews, Catherine A.; Evans, Robert J.; Walker, Stephen J.
Abstract : Interstitial cystitis/bladder pain syndrome is a poorly understood chronic pain condition. While patients experience chronic pain in their bladders and changes to their urinary habits, they also commonly experience widespread pain and issues beyond their bladder. The cause(s) of these symptoms is not well understood. Our research found evidence that patients with interstitial cystitis commonly have damage/thinning to the nerves in their skin, which is associated with being chronically fatigued. This finding may explain some of the widespread symptoms these patients experience. Abstract : Importance: The pathophysiology of interstitial cystitis/bladder pain syndrome (IC/BPS) is imperfectly understood. Recent studies reported that small-fiber polyneuropathy (SFPN) is common in fibromyalgia, a condition commonly comorbid with IC/BPS. Objective: The objective of this study was to determine the prevalence of SFPN in a large cohort of IC/BPS patients. Methods: Adults diagnosed with IC/BPS scheduled to undergo either therapeutic hydrodistention (n = 97) or cystectomy with urinary diversion (n = 3) were prospectively recruited to this study. A skin biopsy obtained from the lower leg was used for intraepidermal nerve fiber density measurement. Small-fiber polyneuropathy (+/−) status was determined by comparing linear intraepidermal nerve fiber density (fibers/mm 2 ) with normative reference values. Demographic information, medical history, and diagnoses for 14 conditions (both urologic and nonurologic) known to co-occur with IC/BPS were documented from self-report and electronic medical record. Results: In this large cohort of patients with IC/BPS, 31% (31/100) were positive for SFPN. Intraepidermal nerve fiber density was below the median for age and sex in 81% (81/100) of patients. Approximately one-third (31%) of SFPN + patients reported co-occurring chronic fatigue syndrome, compared with 10.6% of the SFPN − group ( P = 0.034). Small-fiber polyneuropathy–positive patients reported significantly fewer allergies than SFPN − patients (37.9% vs 60.6%; P = 0.047). There were no significant differences in bladder capacity or Hunner lesion status between the SFPN + and SFPN − subgroups. Conclusions: Small-fiber polyneuropathy is a common finding in patients with IC/BPS, and SFPN status is significantly correlated with co-occurring chronic fatigue syndrome and negatively correlated with the presence of allergies in this population.